Deimplementing Untested Practices in Homecare Services: A Preobservational-Postobservational Design. (19th March 2019) - Guay, Manon; Ruest, Mélanie; Contandriopoulos, Damien
Abstract : Introduction . With community-dwelling elders waiting to adapt their bathroom, Health and Social Services Centers in Quebec (Canada) combined human resources through cross-skilling within interdisciplinary teams. To this end, occupational therapists implemented in-house "tools" to support nonoccupational therapists in selecting bathing equipment. However, unknown psychometric properties of those in-house "tools" cast doubt on the quality of service provided to elders. Little is also known about the best processes to use to support the deimplementation of such nonevidence-based practices. This study presents the effect of a knowledge transfer and exchange intervention designed to deimplement in-house "tools" and replace them with an evidence-based tool (Algo). Methods . Censuses were conducted with the 94 Health and Social Services Centers of Quebec providing homecare services, before and after the knowledge transfer and exchange intervention (2009-2013). In 2013, the deimplementation of in-house "tools" and their replacement by Algo were measured with Knott and Wildavsky's levels of utilization. Results . Cross-skilling within interdisciplinary teams increased between censuses (87% to 98%), as did use of in-house "tools" (67% to 81%). Algo's uptake started during the knowledge transfer and exchange process as 25 Health and Social Services Centers achieved the first level of utilization. Nonetheless, no Health and Social Services Center deimplemented the in-house "tools" to use Algo. Conclusion . The knowledge transfer and exchange process led to the development of a scientifically sound clinical tool (Algo) and challenged the status quo in clinical settings regarding the use of nonevidence-based practices. However, the deimplementation of in-use practices has not yet been observed. This study highlights the need to act proactively on the deimplementation and implementation processes.